Diagnostic Challenges of Acute Limb Ischemia Rutherford IIa with Pancytopenia - Nyoman Budhi Wirananda Setiawan; I Ketut Andriyasa; Putu Arya Nugraha; Made Widiastika; Dwiputra Yogi Pramarta; Ni Made Nova Andari Kluniari (Ganesha Medicina, 2026)
Pancytopenia is a hematological condition associated with impaired blood cell production and an increased risk of bleeding, making arterial thrombosis an uncommon clinical finding. The coexistence of pancytopenia and acute limb ischemia presents significant diagnostic and therapeutic challenges. This case report aims to describe the complexity of diagnosing and managing acute limb ischemia in a patient with underlying pancytopenia. An 87-year-old woman with a known history of pancytopenia presented with pain and blackish discoloration of the right great toe. Laboratory evaluation revealed severe anemia, leukopenia, and thrombocytopenia. Doppler ultrasonography demonstrated atherosclerosis with multiple thrombi in the femoral and anterior tibial arteries. Peripheral blood smear showed abnormal erythrocyte and platelet morphology. A diagnosis of acute limb ischemia with pancytopenia was established. Management posed a clinical dilemma, as anticoagulation was required to prevent ischemic progression, while severe thrombocytopenia increased the risk of bleeding. After multidisciplinary discussion, conservative treatment with heparin was initiated. The patient’s family declined invasive diagnostic and therapeutic procedures, including bone marrow examination and thrombectomy. This case highlights the importance of considering a broad differential diagnosis in pancytopenia and emphasizes the need for individualized management strategies when acute limb ischemia occurs in patients with high bleeding risk.